The impact of enterprise digital transformation on employees’ intrinsic motivation: the mediating role of justice perceptions - Chang, Xiaorui; Yang, Junqing (Frontiers in Psychology, 2025)
Enterprise digital transformation is an important means for enterprises to seek innovation and development, and intrinsic motivation serves as the foundation for employees’ innovation, a crucial indicator of a successful enterprise digital transformation is the enhancement of employees’ intrinsic motivation. However, there are relatively few existing studies focusing on the positive relationship between enterprise digital transformation and employees’ intrinsic motivation, so it is necessary to further explore the mechanism through which enterprise digital transformation stimulates employees’ intrinsic motivation. Based on the structural intrinsic motivation perspective, data from 607 in-service employees were collected using a three-wave approach. The research results, derived from path analysis and moderating effect analysis methods, indicate that enterprise digital transformation has an motivational effect on employees’ intrinsic motivation, and employees’ distributive justice, procedural justice, and interactional justice perceptions all play significant mediating roles, while information processing job characteristics show significantly different moderating effects on different motivational paths: When information processing are low, the distributive justice path loses its motivational effect, while the motivational effect of the interactional justice path significantly decreases when information processing are high, and the moderating effect on the procedural justice path is always insignificant. These findings highlight the micro-positive effects of enterprise digital transformation, provide new explanations for the existing research disagreement, and provide theoretical and practical insights for implementing rational, orderly, and targeted digital transformation strategies for employees with different job characteristics in practice.